Akkermansia muciniphila improves heat stress-impaired intestinal barrier function by modulating HSP27 in Caco-2 cells. (April 2023) - Peng, Mian; Yi, Wanhua; Murong, Min; Peng, Na; Tong, Huasheng; Jiang, Mengliu; Jin, Di; Peng, Suliu; Liang, Weifen; Quan, Jingwen; Li, Muman; Shi, Linna; et al.
Abstract: Objective: Heat stress causes an elevation of intestinal epithelial barrier permeability and leads to multiple organ dysfunction in heatstroke. Akkermansia muciniphila ( A. muciniphila ) plays a role in maintaining intestinal integrity and improving the inflammatory state. This study aimed to investigate whether A. muciniphila could alleviate heat stress-induced dysfunction of intestinal permeability in Caco-2 monolayers and have the preventive effects on heatstroke. Methods: Human intestinal epithelial Caco-2 cells were preincubated with live or pasteurized A. muciniphila then exposed to heat stress at 43 °C. Transepithelial electrical resistance (TEER) and the flux of horseradish peroxidase (HRP) across cell monolayers were measured to determine intestinal permeability. The levels of the tight junction proteins Occludin, ZO-1 and HSP27 were analyzed by Western blotting. These proteins were immunostained and localized by fluorescence microscopy. TJ morphology was observed using transmission electron microscopy (TEM). Results: Both live and pasteurized A. muciniphila effectively attenuated the decrease in TEER and impairment of intestinal permeability in HRP flux induced by heat exposure. A. muciniphila significantly elevated the expression of Occludin and ZO-1 by promoting HSP27 phosphorylation. The distortion and redistribution of tight junction proteins and disruption of morphology were also effectively prevented by pretreatment with A. muciniphila . Conclusion: This study indicates for the first time that both live and pasteurized A. muciniphila play an important protective role against heat-induced permeability dysfunction and epithelial barrier damage.